Bifunctional noble metal/zeolite catalysts for upgrading low-quality diesel fractions via selective opening of naphthenic rings - Pergher, Sibele Berenice Castellã (2016)
Current regulations for diesel fuels primarily involve severe reductions in the concentrations of sulfur and polyaromatics and a minimum cetane number (51 according to current EU standards). Low-quality distillate fractions, such as the LCO fraction abundantly produced in fluid catalytic cracking (FCC) units, cannot be directly used as a blending diesel component due to their high polyaromatics content and consequently poor cetane number (CN < 25) and ignition quality. For such fractions, the increase in CN achieved by deep hydrogenation of the polyaromatics is not enough to meet the fuel specifications. Further upgrading through selective ring opening (SRO) of the produced naphthenes has been proposed as a suitable technological solution to bring the CN to the required values. As will be shown in this article, bifunctional catalysts based on noble metals loaded on acidic zeolites (and mesoporous molecular sieves) exhibit good prospects for the SRO of multi-ring naphthenes as those contained in hydrogenated distillates. Moreover, the high hydrogenation ability of the noble metal(s) makes these bifunctional catalysts suitable for the coupled hydrogenation of (poly)aromatics and the subsequent opening of the naphthenic rings. As will be illustrated here for model naphthenic and aromatic compounds, fine tuning of the hydrogenation and hydrogenolysis activities of the metallic function and the acidity and porous structure of the molecular sieve carrier becomes crucial for achieving optimum performance in SRO reactions. Finally, the relevant issue of the sulfur tolerance of these noble metal-based bifunctional SRO catalysts and their performance in the upgrading of sulfur-containing industrial feedstocks will also be addressed in this perspective article